BRAZIL-FINLAND DOSSIER: TRENDS, PERSPECTIVES AND CHALLENGES OF THE EDUCATION FOR THE 21ST CENTURY - Chediak, Sheylla; Bizelli, Jose Luis [UNESP]; Ryymin, Essi (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2018)
Brazil-Finland Dossier, a bilingual (Portuguese and English) edition of Revista Ibero-Americana de Estudos em Educacao (RIAEE), brings the Education for the 21st Century to discussion, focusing on five interconnected subjects of interest: Learning Communities, curriculum innovation, internationalization of education, Project-Based Learning/Problem-Based Learning (PBL) and educational technologies within a student-centered approach. Its aim is to present teacher-researchers' studies and experiences, taking their teaching practices as data-generating that are relevant to investigations, associated with national and international research, especially between Brazil and Finland. Studies carried out in various regions of Brazil and/or Finland bring relevant contributions to support collaborative research programs and actions in Education for the 21st Century.
Keywords: Education for the 21st Century; Brazil; Finland